Enabling Distributed Teams – A Process Model for Early and Continuous Method Validation. (May 2022) - Duehr, K.; Grimminger, J.; Rapp, S.; Albers, A.; Bursac, N.
Abstract: Neglecting challenges of distributed collaboration can lead to significant efficiency and effectiveness losses in agile, distributed development teams. The EDiT method provides support for improving distributed collaboration of development teams. To ensure acceptance, applicability, and contribution to success in industrial development practice, it is necessary to validate the EDiT method. The goal of this contribution is the development of a process model for early and incremental validation of the EDiT method in the field finally leading to a validation of the EDiT method itself.